Enhancing Occupational Therapy Students' Knowledge, Competence, Awareness, and Interest in Accessibility - Michal Avrech Bar; Navah Z. Ratzon (SAGE Publishing, 2016)
Objective/Background: The purpose of this study was to assess whether the incorporation of an environmental assessment for accessibility, as part of an "Activity Analysis" course, would enhance new students' knowledge, competence, awareness, and interest in accessibility issues for people with disabilities. Methods: In this research, we included an out-of-class training of environmental assessment for accessibility. One hundred and two 1st-year occupational therapy students at Tel Aviv University participated in this research. Of the 102 participants, 56 experienced the training and 46 did not but attended the regular Activity Analysis course. The students explored a typical community environment, during which a specific checklist was used for assessing levels of accessibility. The "Accessibility-Knowledge Competence Awareness and Interests" questionnaire was administered before and after the course to both groups. Results: Students who participated in the out-of-class training showed significant increases in their knowledge, competence, and partial awareness of accessibility and also had better grades in two separate courses that required knowledge of accessibility. There was no significant difference in the results of the Accessibility-Knowledge Competence Awareness and Interests before and after the Activity Analysis course in the control group. Conclusion: The findings of the current study support the contribution of teaching 1st-year occupational therapy students the principles and practices of accessibility for people with disabilities, by improving their knowledge and level of competence at this early stage of their professional lives. Further studies are needed, however, to determine the optimal course of implementation in order to enhance awareness and interest in the subject of accessibility.